(untitled) (CAHIERS MAGELLANES-NS, 2024)
In the ever-evolving landscape of digital marketing, Small and Medium Enterprises (SMEs) are continuously seeking innovative strategies to enhance their market presence, boost revenues, and stay competitive. Among the myriad of digital marketing approaches, affiliate marketing has materialized as a compelling and lucrative avenue for SMEs to connect with their TGA (Target Group Audience), foster brand visibility, and drive business growth. This research focuses on exploring the effectiveness of affiliate marketing within the diverse industrial sectors of Gujarat, India. Gujarat, renowned for its entrepreneurial spirit and diverse industrial activities, provides a unique backdrop for investigating the adoption and impact of affiliate marketing in the SME sector. With a robust presence in manufacturing, services, technology, and retail, the SMEs in Gujarat operate in a dynamic environment, navigating challenges and opportunities that shape their marketing strategies. Affiliate marketing, as a performance-based strategy, involves collaborating with external partners (affiliates) who endorse a company's products in barter for a commission for each successful sale or lead generated. This decentralized and results-driven approach has garnered attention for its potential to offer a high return on investment (ROI) and a measurable impact on key business metrics.